PARTIAL LEAST SQUARES - MULTIGROUP ANALYSIS ON THE EFFECT OF LEADERSHIP ON WORK CULTURE AND LECTURER PERFORMANCE - Hairur Rahman; Angga Dwi Mulyanto; Sri Harini; Fachrur Rozi; Bambang Widjanarko Otok; Jerry Dwi Trijoyo Purnomo (PATTIMURA UNIVERSITY, 2026)
Higher education institutions depend on leadership to build their organizational culture and achieve better employee performance. However, there remains limited understanding of how the impact of leadership may vary across institutional contexts. This research employs Partial Least Squares - Multigroup Analysis (PLS-MGA) to explore the effects of leadership on work culture and lecturer performance in two Indonesian universities: UIN Maulana Malik Ibrahim and IAIN Ponorogo. A multistage random sampling of 272 lecturers was conducted. The methodological approach allowed for a robust comparative analysis between the institutions. The results reveal that leadership exhibits powerful positive relationships with work culture and lecturer performance in both institutions. Leadership explains 38.7% of work culture variability at IAIN Ponorogo, but only 18.6% at UIN Maulana Malik Ibrahim. These findings underscore the need for context-sensitive leadership development strategies and provide a foundational contribution for future research in higher education leadership and performance.